2022
DOI: 10.3390/jcm11164759
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cells Profile in Adult Atopic Dermatitis and Effect of IL4-IL13 Inflammatory Pathway Inhibition In Vivo: Prospective Case-Control Study

Abstract: Atopic dermatitis (AD) is an inflammatory disease that typically begins in childhood and may persist into adulthood, becoming a lifelong condition. The major inflammatory mediators of AD are known to be interleukin IL4 and IL13, so Dupilumab, which is able to inhibit both interleukins by blocking the shared IL4Rα subunit, has become an attractive option for treating AD. Mesenchymal stem cells (MSCs) are involved in the onset and development of AD by secreting specific interleukins. The aim of this study was to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 59 publications
3
3
0
Order By: Relevance
“…[32] The fact that DPMSCs exosomes change the Th2 responses in the inflammatory tissue area in dental nickel hypersensitivity toward Th1 is compatible with studies in the literature. [32,33] In this study, IL-4-secreting CD4+ T lymphocyte ratios significantly decreased for dental nickel hypersensitivity in the experimental group exosome applied together with the hydrogel (Group 4) and in the group treated with exosome alone (Group 6) after the seventh day (in the results of the 14th day) compared to (Group 3). The results obtained in the immunological analyzes are supported by the results obtained in the immunohistochemical studies.…”
Section: Discussionsupporting
confidence: 86%
“…[32] The fact that DPMSCs exosomes change the Th2 responses in the inflammatory tissue area in dental nickel hypersensitivity toward Th1 is compatible with studies in the literature. [32,33] In this study, IL-4-secreting CD4+ T lymphocyte ratios significantly decreased for dental nickel hypersensitivity in the experimental group exosome applied together with the hydrogel (Group 4) and in the group treated with exosome alone (Group 6) after the seventh day (in the results of the 14th day) compared to (Group 3). The results obtained in the immunological analyzes are supported by the results obtained in the immunohistochemical studies.…”
Section: Discussionsupporting
confidence: 86%
“…MSCs are multipotent cells residing in multiple tissues with the capacity for selfrenewal and differentiation into various cell types [9,10]. Our previous works confirmed that different pathologies, ranging from the dermatologic to the fibrotic ones [11][12][13][14][15][16][17][18][19][20], arise at the staminal level: MSCs show the same dysregulated pathological properties found in differentiated cells, opening up the hypothesis that the onset of the diseases could be backdated at the stem level.…”
Section: Introductionsupporting
confidence: 53%
“…Starting from these considerations, today, dealing with AD is more than “treating chronic eczema”. The therapeutic strategies available and those that will appear soon have the ambition to modify not only the clinical course but also the natural history of the disease, preventing the cumulative burden that the disease has on the lives of affected patients [ 71 , 72 ]. Understanding AD pathogenesis in depth may represent a starting point that is useful for understanding how the therapeutic panorama of AD is being enriched, through a “bench to bedside” journey [ 72 ].…”
Section: Discussionmentioning
confidence: 99%